Ловушка для Слепого: [роман] / А. Воронин - Воронин Андрей (Современный литератор, 2000)
Экземпляры: аб. (2005) / Инвентарный номер: 49176 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: В 75 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44